Modern Management Techniques and Tools for Color Implementation in the Publication of Library Articles - Arumugam, J.; Radha, L (Science and Technology: Developments and Applications Vol. 4, 2025)
This paper describes color management and the compounds used for publications. One of the crucial tools for publishing is desktop publishing, and how it handles color standards is quite significant. The main focus of this paper is to explore the primary colors, secondary colors, process colors, color gamut’s, device-dependent or independent solutions, color conversion from one device to another device, and creating the profile. It also explains the characterization of colors, color management principles, standards, editing tools and their usage. This paper also projects an overview of using publication software such as Adobe Photoshop, Illustrator, and In Design to create library internal publications.